IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF MELALUI METODE PROBLEM BASED LEARNING PADA MATERI MOMENTUM IMPULS TERHADAP HASIL BELAJAR SISWA - Kasanah, Nur; Sari, Novita Risna; Supriadi, Bambang; Hadiyanto, Hadiyanto (Universitas Jember, 2024)
This research aims to evaluate the improvement in student learning outcomes in physics subjects using the PBL and E-LKPD methods. This research was conducted through Classroom Action Research (PTK) at SMA Negeri 2 Jember. The research results showed an increase in student learning outcomes from the medium category in the first cycle to the high category in the second cycle. Thus, the PBL learning model assisted by E-LKPD is effective in improving student learning outcomes in physics subjects. The conclusion of this research is that the PBL learning method assisted by E-LKPD can improve student learning outcomes in physics subjects. It is hoped that the results of this research can be used as material for consideration and input for educators in implementing the learning process. Keywords: PBL. E-LKPD, PTK, Learning outcomes